Reducing COVID-19 vaccine hesitancy and improving vaccine uptake in Nigeria - Amenze Eguavoen; Heidi J. Larson; Fejiro Chinye-Nwoko; Toluwanimi Ojeniyi (AOSIS, 2023)
By May 30, 2022, there were 526,182,662 confirmed COVID-19 cases and 6,286,057 deaths globally; of which Nigeria had recorded 256,028 confirmed cases and 3143 deaths. By the same time, Nigeria had received a total of 93.9 million doses of the COVID-19 vaccine, enough to vaccinate 25% of the population; however, only 27.4 million people (13.3% of the population) had received at least one dose of the vaccine. This article examines available evidence on COVID-19 vaccine hesitancy in Nigeria and makes recommendations for improving its uptake. Major causes of COVID-19 vaccine hesitancy identified in Nigeria were concerns around vaccine efficacy and safety, disbelief in the existence and severity of the disease, and distrust of the government. To reduce COVID-19 vaccine hesitancy and improve vaccine coverage in Nigeria, mapping vaccine acceptance and hesitancy across geographies and demographics is needed, as well as increased stakeholder communication, and effective community engagement.